2021
DOI: 10.1212/nxi.0000000000001089
|View full text |Cite
|
Sign up to set email alerts
|

Neuromyelitis Optica Spectrum Disorders in Africa

Abstract: Background and ObjectivesNeuromyelitis optica (NMO) is a CNS inflammatory disease that predominantly affects the optic nerves and the spinal cord. It is more frequent in Asian and African populations than in European ones. Data on epidemiology, clinical presentation, additional investigations, and treatment in the African continent are scarce. We aim to (1) collect and analyze published data on neuromyelitis optica spectrum disorder (NMOSD), (2) indicate challenges in the diagnosis and management, and (3) disc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 54 publications
1
2
0
Order By: Relevance
“…7,22 Our findings suggest that a 28% of NMOSD patients may be Black Americans, which is more conservative than the 37% noted in a multicenter observational study of 187 patients seen at facilities in Baltimore, MD, Rochester, MN, and Dallas, TX, USA. 23 Also, our and other Afro-American prevalence estimates are remarkedly higher than those for African populations (0.004–0.2 per 100,000), 6 suggesting that genetic admixture and European ancestry may be a predisposing risk factor, which is similar to what has been observed in MS. 24,25 A notable difference with the more common MS (2018 age/sex-adjusted US prevalence 219 per 100,000) is that the prevalence of MS is higher in White Americans (284 per 100,000) than in Black Americans (226 per 100,000). 16 With respect to Asian Americans, our US prevalence estimates (9.4 per 100,000) were higher than those reported for country-specific Asian populations (e.g.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…7,22 Our findings suggest that a 28% of NMOSD patients may be Black Americans, which is more conservative than the 37% noted in a multicenter observational study of 187 patients seen at facilities in Baltimore, MD, Rochester, MN, and Dallas, TX, USA. 23 Also, our and other Afro-American prevalence estimates are remarkedly higher than those for African populations (0.004–0.2 per 100,000), 6 suggesting that genetic admixture and European ancestry may be a predisposing risk factor, which is similar to what has been observed in MS. 24,25 A notable difference with the more common MS (2018 age/sex-adjusted US prevalence 219 per 100,000) is that the prevalence of MS is higher in White Americans (284 per 100,000) than in Black Americans (226 per 100,000). 16 With respect to Asian Americans, our US prevalence estimates (9.4 per 100,000) were higher than those reported for country-specific Asian populations (e.g.…”
Section: Discussionsupporting
confidence: 82%
“…4 This rare disease affects all populations; however, the burden varies across geographic and racial/ethnic populations, from 0.004/1,000,000 in Ethiopia to 10/100,000 in Martinique, and it disproportionately affects females. 57 Within the United States, there have been two epidemiologic studies but unfortunately their prevalence estimates are remarkably different. In a landmark population-based study of residents of Olmsted County, Minnesota, the 2011 NMOSD age- and sex-adjusted prevalence was 3.9 per 100,000, with a higher prevalence in Black residents (13 per 100,000) than in White residents (4 per 100,000).…”
Section: Introductionmentioning
confidence: 99%
“…12,13 A study of NMOSD in Africa found that the NMO-to-MS ratio is higher in sub-Saharan Africa compared with northern African countries. 14 These studies from around the world highlight differences in the epidemiology, etiologies, and characteristics of ON and its associated diseases among different populations. In any case, it is critical to make the underlying diagnosis as early as possible and to initiate appropriate therapy to protect vision and reduce the risk of ON recurrence and other neurologic sequelae.…”
mentioning
confidence: 99%